Reexamining The Art Of The Amoghapāśa Maṇḍala Assembly Of The 13th Century From Indonesia - Sholah, Ahmad Kholdun Ibnu (Badan Riset dan Inovasi Nasional (BRIN), 2025)
This article discusses the style and iconography of the statues from Candi Jago, consisting of Amoghapāśa and his attendants, and their later copies. It departs from the notion that the new transmission of esoteric Buddhism in the thirteenth century from Northeast India to Java brought along iconographic programs as well as artistic elements. However, the problem of whether such artistic influence can be attested remains disputed among scholars. Using both formal and comparative analysis of the statues’ photographic reproduction, this paper re-examines the style of the Amoghapāśa maṇḍala assembly to unravel the problem of locating the Pāla influence. It begins by tracing the development of the cult of Amoghapāśa and its eight-armed form, following the notion of the movement of Buddhist masters seeking refuge to explain its re-emergence in the thirteenth-century Java. Finally, it elaborates on the theories concerning the style of Candi Jago statues and their later copies related to the presence of Pāla style elements. It concludes that the so-called Pāla elements on the statues reflect the creative force of Javanese artisans in incorporating these new elements into their artworks.